In Silico Analysis of Moringa oleifera Leaf Phytochemicals as Potential DNA Gyrase Inhibitor in Salmonella typhi - Meike Tiya Kusuma; Muzid Syauqil Umam; Damiana Nofita Birhi (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Salmonella typhi is an infectious bacterium leading to typhoid fever, that is increasing in cases worldwide each year. Due to the resistance to antibiotics, the discovery of safer and efficacious drugs remains important. This study evaluates the potential interaction of M. oleifera phytochemical compounds against DNA gyrase of Salmonella typhi using an in silico molecular docking approach. Ligand’s phytochemicals were retrieved from the PubChem database, while the three-dimensional structure of DNA Gyrase subunit A and subunit B were obtained from the Protein Data Bank (PDB ID: 5ZJT and 6J90). Molecular docking was done using PyRx software and BIOVIA Discovery Studio as visualization software. Phytochemical compounds that had higher predictive binding affinity to DNA gyrase subunit A were Naringenin (∆G=-7.9 kcal/mol), 6-Prenylnaringenin (∆G=-8.1 kcal/mol), 6-Methoxypodophyllotoxin (∆G=-7.9 kcal/mol). Brefeldin A- DNA gyrase subunit A complex had the same binding affinity to ciprofloxacin (∆G=-7.7 kcal/mol). Phytochemical compounds that had higher predictive binding affinity to DNA gyrase subunit B were Naringenin (∆G=-8.9 kcal/mol), 6-Prenylnaringenin (∆G=-8.8 kcal/mol), 3',4'-Dimethoxy-7-hydroxyflavone (∆G=-8.6 kcal/mol), Sinapoyl malate (∆G=-7.8 kcal/mol), and Sinapoyl malate-4'-methyl ester (∆G=-8.3 kcal/mol). These findings suggest that phytochemical compounds from M. oleifera leaves may act as potential DNA gyrase inhibitors. However, further in vitro and in vivo validation is required to confirm its antibacterial activity.